Open Access Book Adoption in the Classroom: Sylla’s Innovative Approach to Personalized Discovery - Mosterd, Max (Septentrio Conference Series, 2024)
Abstract: The higher education landscape is experiencing a significant shift towards open and affordable learning resources, driven by technological advancements and economic pressures. The situation calls for solutions that make real impact, including repurposing and making better use of existing materials available online. With nearly 100,000 open access (OA) books available through the Directory of Open Access Books (DOAB), there is an extensive pool of freely accessible scholarly materials. However, the integration of these resources into higher education curricula has not kept pace with their production, primarily due to discovery and adoption challenges faced by faculty. This presentation introduces Sylla, an innovative technology solution designed to bridge the gap between OA book availability and classroom adoption. Developed in collaboration with universities and faculty members, Sylla leverages new technologies to create a personalized discovery experience tailored to specific syllabi and learning objectives. We will demonstrate how Sylla addresses key barriers to OA book adoption in higher education: • Time Constraints: By analyzing course syllabi and providing a curated selection of the most relevant resources, Sylla significantly reduces the time faculty need to spend on resource discovery. • Quality Concerns: The system draws from trusted OA databases and provides detailed explanations of each resource’s relevance to the syllabus, ensuring high-quality matches. • Contextual Fit: Sylla offers granular breakdowns of how recommended resources align with learning objectives and teaching topics, facilitating easier assessment and adoption. • Supply Limitations: By recontextualizing existing OA resources such as monographs and articles for teaching needs, Sylla expands the pool of suitable materials for diverse courses. We will present results from recent pilots at Coventry University in the UK, where Sylla demonstrated significant success in promoting OA book adoption. At Coventry’s School of Business and Law, 10 out of 16 faculty members committed to using OER in their upcoming term as their core course resource, resulting in 66% cost savings and thousands of students benefiting from OER-enabled courses. The relevance of this work extends beyond cost savings. By facilitating easier discovery and adoption of OA books, Sylla empowers faculty to create more personalized and diverse learning experiences. It also supports the broader movement towards open scholarship and affordable learning, aligning with institutional goals to reduce student costs while maintaining educational quality. Looking ahead, we’ll discuss how Sylla and similar AI-driven platforms could transform course preparation, enabling more responsive and adaptable curricula. We’ll also address the importance of balancing openness with sustainability, exploring models that support continued creation and maintenance of high-quality OA resources. See this presentation in this video recording.